Comparing the Effects of Commercially Available and Custom-Made Video Prompting for Teaching Cooking Skills to High School Students With Autism. (November 2013) - Mechling, Linda C.; Ayres, Kevin M.; Foster, Ashley L.; Bryant, Kathryn J.
The study compared the effects of using commercially available and custom-made video prompts on the completion of cooking recipes by four high school age males with a diagnosis of autism. An adapted alternating treatments design with continuous baseline, comparison, final treatment, and best treatment condition was used to compare the two procedures. Gains were made by each participant when using both video procedures. However, results indicate that all students performed more steps independently correct when completing recipes with the custom-made video prompts during the comparison condition. During the best treatment condition, recipes initially prepared using the commercially available video prompts in the comparison condition were performed at criterion levels when completed with the custom-made videos prompts. Implications for use and development of commercial and customized video products with attention to the salient features of video prompts are presented.